A Metallo-Dielectric Groove Gap Waveguide Slotted Array Antenna With Hybrid Glide-Symmetric Holes & “Mushroom”-Type Metasurfaces - Panagiotis Petroutsos; Stavros Koulouridis (IEEE Open Journal of Antennas and Propagation)
We present a hybrid multilayer slot array antenna, targeting next-generation wireless communication systems, particularly in mmWave bands like the Ka-band. The hybrid structure utilizes a high-performance metal Groove Gap Waveguide (GGW) feeding network and facilitates the practical manufacturing of slotted antennas and dielectric substrate metasurfaces using printed circuit boards. The proposed antenna incorporates a hybrid glide symmetric holey metasurface into the GGW feeding. This integration addresses assembly challenges between metal and dielectric layers, avoiding delicate welding techniques. It prevents energy leakage between the two different materials, even when a small air gap is maintained between them. The antenna also involves a printed periodic surface comprising ‘Mushrooms’ type cells on a thin dielectric substrate. As an effect, this design reduces mutual coupling between parallel slotted array antennas and provides a more compact structure compared to alternative decoupling methods such as vertical corrugation slots, or horn types. The textured ‘Mushroom’ surface enhances the antenna directivity by 3.4 dB and reduces the level of sidelobes by up to 6.2 dB. Measurement results demonstrate an achieved impedance bandwidth ( $S_{11} \lt -$ 10 dB) of 8.15% within the frequency range of 37.88 GHz to 40.98 GHz. Additionally, the antenna achieves a gain of up to 16.55 dB over the frequency of interest.